Transfer and transformations of oxygen in rivers as catchment reflectors of continental landscapes: A review - Piatka, David; Wild, Romy; Hartmann, Jens; Kaule, Robin; Kaule, Lisa; Gilfedder, Benjamin; Peiffer, Stefan; Geist, Juergen; Beierkuhnlein, Carl; Barth, Johannes (Earth-Science Reviews, 2021)
Oxygen is one of the most crucial elements on earth and equally affects life and inorganic redox processes. After its transition to water with moderate solubility and slow diffusion rates, most aquatic organisms depend on permanent renewal of dissolved oxygen (DO). Recharge of this pivotal aqueous gas may become hampered by anthropogenic and climatic influences with so far unknown consequences for surface freshwater systems and entire ecosystems. Because rivers integrate biogeochemical information of catchments, their oxygen dynamics may also reflect ecosystem and landscape health. Here we summarize the most important sources and sinks of DO and its role in river systems. These considerations also extend to associated water compartments and fluxes including lakes, reservoirs, soils, groundwater and the hyporheic zone. In addition, for continental-scale considerations, we analysed the GLObal RIver CHemistry (GLORICH) database with 170,369 DO measurements. These analyses revealed that DO in rivers relates to water temperature, pH and nutrient availability. On larger scales, it is also influenced by catchment area, slope, ratios of forests to managed land and population density. Our review also highlights important links between physical and biological influences on DO transfer as well as its sources and sinks in streams and rivers. We conclude that DO monitoring should be combined with novel interdisciplinary tracing techniques such as stable isotope ratios, radon gas and biological analyses. Such combined analyses have the potential to improve our understanding of transfer and transformations of oxygen in rivers as essential integrators of landscapes.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anthropogenic pressure; Climate change; Dissolved oxygen; GLObal RIver CHemistry database; Rivers; Transformation; Turnover